Recurrent liver hydatid cyst and port site hydatid cyst in anterior abdominal wall in operated case of laparoscopic cystostomy for liver hydatid cyst: a rare complication - T., Swamy P.; Vagadia, Jayendra G.; Bhatt, Jatin G.; Dave, Jignesh P. (International Surgery Journal, 2021)
Hydatid disease, or echinococcosis, is a widespread zoonotic parasitic disease caused by a tapeworm that continues to be a clinical and public health problem worldwide, especially in areas where animal husbandry and subsistence farming form an integral part of community life. Location of cyst in different organs of body changes the diagnostic and therapeutic management of the cyst. Four treatment options are currently available: radical surgery, conservative surgery, puncture-aspiration-injection-respiration (PAIR), and antiparasitic medical treatment. Surgery is gold standard for liver hydatid cyst and can be done by open/laparoscopic approach. We are reporting a case of recurrence of liver hydatid cyst with port site anterior abdominal wall hydatid cyst in a 40-year-old female patient operated previously for laparoscopic liver hydatid cystectomy. Port site hydatid cyst is a rare complication after laparoscopic hydatid cystotomy, but can occur due to lodgement of scolices at port site while removing daughter cyst at port site of laparoscopy.